2019
DOI: 10.1038/s41388-019-1141-7
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 signaling in breast carcinoma cells promotes tumor growth and invasion by promoting CCL2 and suppressing CD154 effects on the angiogenic and immune microenvironments

Abstract: Breast cancer is the second leading cause of cancer related deaths for women, due mainly to metastatic disease. Invasive tumors exhibit aberrations in recruitment and activity of immune cells, including decreased cytotoxic T cells. Restoring the levels and activity of cytotoxic T cells is a promising anti-cancer strategy; but its success is tumor type-dependent. The mechanisms that coordinate recruitment and activity of immune cells and other stromal cells in breast cancer remain poorly understood. Using the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…Zhu et al pointed out that immune cell recruitment is reduced, while M2-like macrophages are increased in metastatic BC tumors 16 . Brummer et al have revealed that selective targeting of CCR2 impaired BC tumor growth and invasion as well as decreased M2 macrophages-induced angiogenesis 17 . Chen et al revealed that activated M2 macrophages are strongly associated with survival for both Asian and Western patients with BC 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al pointed out that immune cell recruitment is reduced, while M2-like macrophages are increased in metastatic BC tumors 16 . Brummer et al have revealed that selective targeting of CCR2 impaired BC tumor growth and invasion as well as decreased M2 macrophages-induced angiogenesis 17 . Chen et al revealed that activated M2 macrophages are strongly associated with survival for both Asian and Western patients with BC 18 .…”
Section: Introductionmentioning
confidence: 99%
“…CCL2 was identi ed as another proangiogenic factor induced by ETV5 in CRC. CCL2/CCR2 chemokine signaling was proved to promote breast cancer progression by induced angiogenesis [20]. By ELISA assay, we found that attenuation of VEGFA could not affect ETV5-mediated CCL2 secretion, and anti-CCL2 treatment also did not have in uence on ETV5-mediated VEGFA secretion in CRC cells.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, our previous study showed that ETV5 facilitated CRC angiogenesis via PDGF-BB/Src/STAT3/VEGFA signaling pathway [19]. Besides, more and more studies indicated that chemokine signaling played critical roles in tumor angiogenesis, such as CCL2/CCR2 signaling and CXCL11/CXCR7 signaling [20,21]. ETV5 was also reported to regulate chemokines expression of sertoli cell in mouse, such as Ccl7, Ccl9, Ccl12.…”
Section: Introductionmentioning
confidence: 68%
“…Other factors contribute to increase the breast angiogenic microenvironment. For instance, recent studies showed that CCL2/CCR2 signaling in breast cancer cells regulates tumor growth and invasion by promoting angiogenesis through the recruitment and branching of endothelial cells, recruiting and polarizing macrophages to M2 phenotype, and suppressing cytotoxic T-cell activity [156]. Kim et al [157] analyzed both the expression levels of Notch1, a signaling pathway involved in cell proliferation and angiogenesis, and microRNAs-34a in 114 TNBC samples and reported better OS in patients presenting low EC Notch1 (Notch1 microvascular density to CD34 microvascular density ratio) than those with a high ratio, and a significant correlation between high microRNAs-34a levels, decreased vessel formation (low EC Notch1 levels) and higher survival benefit in a lymph-node-positive group [157].…”
Section: Microvascular Density In Tmementioning
confidence: 99%